A clinicopathologic study on SS18 fusion positive head and neck synovial sarcomas. (March 2017) - Owosho, Adepitan A.; Estilo, Cherry L.; Rosen, Evan B.; Yom, SaeHee K.; Huryn, Joseph M.; Antonescu, Cristina R.
Highlights: The 2, 5 and 10-year DSS rates for SS-HN were 97%, 79% and 68%, respectively. Recurrence showed significant effect on DSS. Tumor site was associated with local tumor recurrence. Adjuvant chemotherapy to surgery with RT in high-risk-patients may be beneficial. Abstract: Objective: To determine clinicopathologic factors on survival in patients with head and neck synovial sarcoma. Patients and methods: We retrospectively identified patients with molecularly confirmed synovial sarcomas of the head and neck (SS-HN), either by the presence of SS18-SSX fusion transcript by RT-PCR or SS18 gene rearrangement by FISH, who were managed at our institution over a 20-year period (1996–2015). Kaplan-Meier survival analysis and log-rank test were performed to evaluate variables related to disease specific survival (DSS). Fisher exact test was performed to evaluate variables related to local recurrence. Results: Thirty-four patients (20 males and 14 females, mean of 31 years) with SS18-SSX fusion-positive SS-HN were identified. The parapharyngeal region of the neck was the most common site. The mean tumor size was 4.8 cm (0.8–10 cm). Two-thirds (n = 23) of cases had a monophasic histology. The 2, 5 and 10–year DSS rates were 97%, 79% and 68%. The 5-year DSS rates for the adult/pediatric cohort were 74%/88%. Recurrence showed significant effect on DSS (p = 0.021). There was no significant effect on DSS with age, therapy modality, tumor site, surgical margin, tumor size (⩽5 cm vs. >5 cm) and histopathologic subtype. Tumor site (i.e. skull base/paranasal sinus region) was associated with local recurrence (p = 0.003). Conclusion: In our cohort DSS rate was associated with recurrence. Tumors located in the skull base/paranasal sinus region were associated with a higher rate of local recurrence. Thus appropriate selection of high risk patients who can benefit from multimodality therapies might improve survival.